A PEMBUATAN PUPUK ORGANIK CAIR DARI LIMBAH SAYURAN: PEMBUATAN PUPUK ORGANIK CAIR DARI LIMBAH SAYURAN - Sartono; Elly Istiana Maulida; Septi Kumalasari (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
Community Service entitled Making Liquid Organic Fertilizer from Vegetable Waste involving the Taru Mulyo Farmer Group in Karangpalem village, Kedawung sub-district, Sragen district which cares about environmental conservation, has been carried out on May 25, 2021. The purpose of this activity is to utilize household waste from waste The vegetables are then developed to make liquid organic fertilizer. Thus the environment becomes clean and healthy, and is able to increase the income of partners. The resulting output target is a packaged liquid organic fertilizer product as well as the Adi Widya Service journal, and Presentation at Senadimas. To realize the output targets, the methods applied include counseling, training, mentoring and at the same time direct practice. In order for this partnership program to be sustainable, periodic monitoring and evaluation are carried out.